LEGAL PROTECTION FOR WOMEN VICTIMS OF SEXUAL VIOLENCE IN THE CITY OF MAKASSAR - Badaru, Baharuddin; Rosmiati, Rosmiati; Thalib, Hambai (Jurnal Ilmiah Global Education, 2023)
Research objectives: (1) To analyze and explain whether existing regulations are able to provide protection for women victims of sexual violence. (2) To analyze and explain how the police provide legal protection for women victims of sexual violence. This study uses empirical research methods. This method is used to review or analyze primary data in the form of data in the field where the writer researched and the results of direct interviews and electronic questionnaires (e-questionnaires) submitted to respondents and then connected with secondary data in the form of legal materials to analyze legal protection women victims of sexual violence in the city of Makassar. The results of research related to legal protection for women victims of sexual violence in the city of Makassar have not been maximized, this is because the TPKS Law has not been implemented optimally, and during the last five years, the number of sexual violence has been quite high. In addition, there is no special room for examining victims (taking BAP), so the level of comfort and safety for victims during examinations is still minimal. Research Recommendations: Build a strategy to maximize the implementation of the TPKS Law and Strengthen the Capacity of APH and Facilitators; build maximum coordination of APH and related service institutions.